Controlling crack formation since early ages: contributions of COST Action TU1404 and research project IntegraCrete - Azenha, Miguel (2019)
The present contribution summarizes main activitiesand conclusions brought about by two funded projects: EU-funded COST Action TU1404 ‘Towards the next generation of standards for service life of cement-based materials and structures’ and Portugal-EU funded project IntegraCrete ‘A comprehensive multiphysics and multiscale approach to the combined effects of applied loads and thermal/shrinkage deformations in reinforced concrete structures’